2014
DOI: 10.1088/0004-637x/798/2/80
|View full text |Cite
|
Sign up to set email alerts
|

FORMATION OF S-BEARING SPECIES BY VUV/EUV IRRADIATION OF H2S-CONTAINING ICE MIXTURES: PHOTON ENERGY AND CARBON SOURCE EFFECTS

Abstract: Carbonyl sulfide (OCS) is a key molecule in astrobiology that acts as a catalyst in peptide synthesis by coupling amino acids. Experimental studies suggest that hydrogen sulfide (H 2 S), a precursor of OCS, could be present in astrophysical environments. In the present study, we used a microwave-discharge hydrogen-flow lamp, simulating the interstellar UV field, and a monochromatic synchrotron light beam to irradiate CO:H 2 S and CO 2 :H 2 S ice mixtures at 14 K with vacuum ultraviolet (VUV) or extreme ultravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Quantitative descriptions of the IR spectrum of amorphous H 2 S are surprisingly scarce as shown by tracing the origin of the currently used A′(S-H) band strength. A recent astrochemical paper on sulfur chemistry (Chen et al 2015) used A′(S-H)= 2.0×10 −17 cm molecule −1 for amorphous H 2 S at 14 K, taken from a paper of Jiménez-Escobar & Muñoz Caro (2011). The latter authors derived this value by rescaling one from Smith (1991) of A′(S-H)=2.9×10 −17 cm molecule −1 for crystalline H 2 S at 88 K to amorphous H 2 S at 10 K. Smith, in turn, derived his A′ for amorphous H 2 S by combining all of the band intensities of Ferraro et al (1980) for crystalline H 2 S in the S-H stretching region.…”
Section: H 2 S Resultsmentioning
confidence: 99%
“…Quantitative descriptions of the IR spectrum of amorphous H 2 S are surprisingly scarce as shown by tracing the origin of the currently used A′(S-H) band strength. A recent astrochemical paper on sulfur chemistry (Chen et al 2015) used A′(S-H)= 2.0×10 −17 cm molecule −1 for amorphous H 2 S at 14 K, taken from a paper of Jiménez-Escobar & Muñoz Caro (2011). The latter authors derived this value by rescaling one from Smith (1991) of A′(S-H)=2.9×10 −17 cm molecule −1 for crystalline H 2 S at 88 K to amorphous H 2 S at 10 K. Smith, in turn, derived his A′ for amorphous H 2 S by combining all of the band intensities of Ferraro et al (1980) for crystalline H 2 S in the S-H stretching region.…”
Section: H 2 S Resultsmentioning
confidence: 99%
“…This band is assigned to the C=O stretching mode of OCS, which is observed at 2019 cm −1 in pure OCS ice and shifted to 2046 cm −1 in OCS-H 2 O and OCS-CO 2 mixtures (Ferrante et al 2008). Previous experimental studies reported the formation of OCS after irradiation of ices containing CO or CO 2 as the carbon source and H 2 S or SO 2 as sulfur source (Ferrante et al 2008;Chen et al 2015). Our assignment of the 2040 cm −1 band to OCS is supported by the absence of this band in the infrared spectrum of the irradiated "without H 2 S" mixture, where no sulfur was present.…”
Section: Pure Methanol Icementioning
confidence: 92%
“…The products depend on the initial ice composition, as illustrated in recent experiments (e.g. Garozzo et al 2010;Chen et al 2015). Note that OCS can potentially also be formed by low-temperature surface reactions of CO with S without the need for photolysis or radiolysis.…”
mentioning
confidence: 85%